Experimental Investigation of the Mechanical Failure Behavior of Coal Specimens With Water Intrusion - Yao, Qiangling; Zheng, Chuangkai; Tang, Chuanjin; Xu, Qiang; Chong, Zhaohui; Li, Xuehua (Frontiers in Earth Science, 2020)
Mining fissures formed by coal mining can easily open bedrock and loose aquifers, and can thus cause water–rock interaction. The strength of coal and rock and their pore and fracture development characteristics are closely related to moisture content. Therefore, this paper studied the strength, porosity, fracture propagation, and failure characteristics of coal with different moisture contents. Six representative coal samples with different moisture contents of 0, 3.79, 6.10, 9.17, 11.01, and 11.68% were prepared by non-destructive water immersion experiment, and the samples were analyzed using. Nuclear Magnetic Resonance (NMR) and uniaxial compression acoustic emission experiments. Then, the temporal and spatial variation of the moisture contents of the coal samples and the characteristics of crack propagation and failure were studied before and after water immersion. Non-destructive water immersion and NMR analysis showed that the moisture content increases exponentially with increasing water immersion time and immersion frequency. Additionally, it was shown that with increasing water immersion time and frequency, the moisture distribution within the coal samples changes from uneven to uniform, and micro-pores and meso-pores develop into larger pores with increasing water content. A coupled uniaxial compression–acoustic emission experiment showed that acoustic emissions are closely related to the macroscopic failure mode of the coal sample. With increasing sample moisture content, the degree of sample destruction and the concentration of acoustic emissions both reduced. The increase of moisture content promotes the change of the macroscopic failure mode of the coal samples from tensile failure to tensile–shear composite failure. The results of this study have important reference value for analyzing the stability of coal pillars and surrounding rock under the action of water, and especially for the design of coal pillar dam bodies in coal mines with groundwater reservoirs.